Speaking about sounds: a tool for communication on sound features. (2017) - Carron, Maxime; Rotureau, Thomas; Dubois, Françoise; Misdariis, Nicolas; Susini, Patrick
With the increasing use of digital technologies and smart objects, sound is playing an ever more important role in our everyday life interactions with a given object, human computer interface or space. However, few methodologies exist to work on sound-related issues during the early stages of a design process; manufacturers and sound designers lack a common terminology to describe and sketch sonic ideas. Informed by a review of the academic literature on verbal descriptions of sounds and a series of interviews we conducted with sound practitioners, we propose in the present article a potentially normative lexicon of 35 terms to describe the main sound characteristics. We also present a computer interface presenting the 35 terms illustrated with concrete and abstract sounds. This interface may be used as a tool for communication on sound features in a sound design process but also during training classes on sound education.